Development and application of environmental DNA surveillance for the threatened crucian carp (Carassius carassius). (12th November 2018) - Harper, Lynsey R.; Griffiths, Nathan P.; Lawson Handley, Lori; Sayer, Carl D.; Read, Daniel S.; Harper, Kirsten J.; Blackman, Rosetta C.; Li, Jianlong; Hänfling, Bernd
Abstract: The crucian carp ( Carassius carassius ) is one of few fish species associated with small ponds in the UK. These populations contain genetic diversity not found in Europe and are important to conservation efforts for the species which has declined across its range in Europe. Detection and monitoring of extant crucian carp populations are crucial for conservation success. Environmental DNA (eDNA) analysis could be very useful in this respect as a rapid, cost‐efficient monitoring tool. We developed a species‐specific quantitative polymerase chain reaction (qPCR) assay for eDNA surveillance of crucian carp to enable non‐invasive, large‐scale distribution monitoring. We compared fyke netting and eDNA analysis at ponds with ( n =  10) and without ( n =  10) crucian carp for presence–absence detection. We examined biotic (crucian carp density represented by catch‐per‐unit‐effort [CPUE] estimate) and abiotic influences on eDNA detection probability using a hierarchical occupancy model, and eDNA quantification using a mixed‐effects model. eDNA analysis achieved 90% detection for crucian carp ( n =  10), failing in only one pond where presence was known. CPUE estimate and conductivity had positive and negative influences on eDNA detection probability in qPCR replicates respectively. Similarly, conductivity had a negative effect on DNA copy number, whereas copy number increased with CPUE estimate. Our results demonstrate that eDNA analysis could enable detection of crucian carp populations in ponds and benefit ongoing conservation efforts, but imperfect species detection in relation to biotic and abiotic factors and eDNA workflow requires further investigation. Nonetheless, we have established an eDNA framework for the crucian carp as well as sources of imperfect detection which future investigations can build upon.